Design Aspects of Metal-Free Nitrogen-Based Catalysts and Their Influence on the Yield in the Henry Reaction - Yao, Qiong Ji; Khong, Duc Thinh; Gao, Qi; Judeh, Zaher M. A. (Synthesis, 2014)
Design aspects of metal-free nitrogen-based catalysts and their influence on the yield in the Henry reaction are disclosed. C1-Symmetric, N,N-1,2-disposed amine-imine type catalysts were found to be most efficient. C1-N,N-1,2-Disposed 1,2,3,4-tetrahydro-1,1′-biisoquinoline selectively and efficiently catalyzed the addition of nitromethane to α-keto esters and aldehydes giving exclusively the corresponding β-nitro alcohol adducts in excellent yields under very mild conditions.
Keywords: catalyst design; biisoquinoline; C–C bond formation; Henry reaction; Proton Sponge